EXPLORING THE ROLE OF HEALTHY FOOD KNOWLEDGE ON BEHAVIOR INTENTIONS OF CONSUMER TOWARDS RESTAURANTS - Ishfaq, Umer; Imam, Mudassar; Bashir, Muhammad Atif; Askari, Mahrukh; Ullah, Ihtisham; Shahzadi, Sidra (The journal of contemporary issues in business and government, 2022)
Sustaining customer satisfaction and revisit intentions of the fast food restaurants has become crucial problem for survival in this intense competition. Therefore, this study addressed this problem by conducting this research to investigate the factors effecting customer satisfaction and revisit intentions of the fast food customers in the city of Faisalabad. This study also filled the theoretical gap in the literature by considering Dinex, healthy food knowledge, perceived value’s effect on revisit intentions through mediation of customer satisfaction. For this purpose, quantitative approach was used, and self-administrated questionnaire was provided to the customers of the fast food restaurants in Faisalabad who have at least visited them twice. Sampling technique used for this study was convenient due to the difficulty in finding appropriate sample. 220 of sample size was used after removing inappropriate and unfilled responses. Partial Least Square Structural Equation Modeling (PLS-SEM) was employed through Smart PLS software. Measurement model ensured the validity and reliability of the constructs. Total seven direct and three indirect hypotheses were proposed in the study. Structural model examined the hypothesis testing and its significance. Findings of the study showed that all direct relationships were positive and significant except effect of healthy food knowledge on revisit intentions. Mediation effects of Dinex, healthy food knowledge, perceived value was significant through customer satisfaction on revisit intentions. Implications of the study includes use of this study for enhancing customer satisfaction and revisit intentions of the customers to gain competitive advantage.